Development of Mathematics Teaching Materials on Statistics with A Problem-Solving Approach - Wulan, Indah Indar; Warsito, Warsito; Iskandar, Ratu Sarah Fauziah (Indonesian Journal of Teaching and Learning, 2025)
This study aims to develop mathematics teaching materials on statistics material that is practical, effective, and valid, and suitable as a student learning module. The type of research used is Research and Development (R&D), which involves developing teaching materials in the form of modules on the subject of statistics. The model used in this teaching material research is the 4-D development model (four D models). This research model has four stages of research, namely 4-D development (four D Models), including define, design, develop, and disseminate. Based on this study, it was found that the Module with a problem-solving approach to statistics material developed by researchers with the 4D model modified into 3D was declared valid by material experts, and media experts with Very Good criteria, and based on the assessment of education experts, namely teachers and students. A module with a problem-solving approach to statistics material, developed by researchers, was declared practical. This means that the Module developed by researchers makes it easier for students to learn and can increase students' interest and motivation in learning mathematics, especially statistics material. This study aims to develop mathematics teaching materials on statistics material that is practical, effective, and valid, and suitable as a student learning module. The type of research used is Research and Development (R&D), which involves developing teaching materials in the form of modules on the subject of statistics. The model used in this teaching material research is the 4-D development model (four D models). This research model has four stages of research, namely 4-D development (four D Models), including define, design, develop, and disseminate. Based on this study, it was found that the Module with a problem-solving approach to statistics material developed by researchers with the 4D model modified into 3D was declared valid by material experts, and media experts with Very Good criteria, and based on the assessment of education experts, namely teachers and students. A module with a problem-solving approach to statistics material, developed by researchers, was declared practical. This means that the Module developed by researchers makes it easier for students to learn and can increase students' interest and motivation in learning mathematics, especially statistics material.